Contribution of Community Sport to the Integration of Immigrants - Ajiee, Richard Opara (Auckland University of Technology, 2020)
Sport enjoys widespread popularity as a powerful tool for social change, especially for the integration of immigrants. This widespread assumption has led to substantial investment in the production and promotion of sport at the community level. However, concerns remain around the social impact of sport participation, especially in the area of integration of immigrants. Although previous studies have attempted to provide empirical evidence on the social impact of sport, there still remains a shortage of scientific evidence underpinning the process of social change through sport, especially in the area of integration of immigrants. This has prompted many scholars to call for studies to address this shortfall. Thus, the main aim of this study is to understand the contribution of community sport to the integration of immigrants in New Zealand. In particular, it investigates the role of sport as a vehicle of integration and acquisition of social capital. The study utilises a qualitative research approach for the ethnographic exploration of the efficacy of sport as a vehicle for the integration of immigrants and acquisition of social capital. The lived experiences of seven immigrants were gathered through multiple unstructured in-depth interviews over a twelve-month period. Creative Analytical Practice (CAP) was adopted to share the stories of the lived experiences of the immigrants in this study. The seven stories shared within this thesis provide nuanced insights into the role of sport, social capital, and immigrant integration in New Zealand. They illuminate the role sport played in the journey of the immigrants in New Zealand. Further, through the stories shared, the role of sport in immigrants’ acquisition of social capital is clearly explicated. The findings indicate that first contact with sport was crucial to the acquisition of social capital and the integration of immigrants through sport. It is argued that immigrants must first and foremost access sport before proceeding to utilising it as a vehicle of integration and acquisition of social capital. It was found that school plays a major role in offering young (school-aged) immigrants access to sport while adult (older) immigrants relied on media to gain knowledge about sporting opportunities in their new community. Also, the findings reveal that while young (school-aged) immigrants accessed sport without the intention of acquiring social capital, adult (older) immigrants on the other hand, accessed sport with the intention of acquiring social capital. Further, the findings reveal that immigrants were able to acquire social capital through their participation in sport. It was found that immigrants were able to establish networks and relationships with the host community through their sport participation. One way they were able to develop these relationships was through their participation in post-game social activities. It is revealed that during post-game social rituals, the possibility of developing bonding and bridging capital increases. Similarly, findings shed light on the attitude of the host community and the implication on the integration of immigrants. A warm attitude as experienced by most of the immigrants in the study would facilitate the acquisition of social capital and subsequent integration. In contrast, a cold attitude would impact on the sense of belonging of the immigrant and hinder integration. Perhaps one of the most important role sport plays in the process of integration of immigrants is creating a sense of belonging. In addition, the findings shed light on how sport helped immigrants to develop language skills, secure employment, learn about the New Zealand (Kiwi) culture and develop a sense of belonging. Overall, through the adoption of Creative Analytical Practice (CAP), this study was able to share the lived experiences of immigrants and the role of sport in the process of their integration into New Zealand. The study clearly shows that sport can contribute to the generation of social capital and integration of immigrants. Thus, this thesis contributes to the body of knowledge by providing further empirical evidence on sport as a vehicle for social change. The development and introduction of the social capital - integration model is another major contribution of this study. It is expected that the model could be used by future studies on sport and integration of immigrants.
Keywords: Sport for integration; Social capital; Sport for social change; Creative analytical practice; Immigrants